Results of Endometrial Sampling in Patients with Abnormal Premenopausal Hemorrhages: Analysis of 1492 Cases - Mehmet Şükrü Budak; Mehmet Baki Şentürk; Sedat Akgöl; Mehmet Nafi Sakar; Ali Emre Tahaoğlu; Cihan Toğrul; Ayhan Yıldırım (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The aim of the study is the evaluation of histopathologic pattern in premenopausal patients subjected to endometrial sampling due to abnormal uterine hemorrhages.